On some problems in economic relations between the Turkic-speaking Central Asian republics (Journal of Oriental Studies, 2016)
Despite the institutional problems of Central Asia is one of the fastest growing regions in the world economy.The rich presence of natural energy resources and cheap labor could contribute to the future prosperity of the region.If you look at the basis of economic relations between the Turkic republics, something immediately apparent different economic model and strategy, sometimes sharply contrary to each other.
Keywords: Central Asia; Turkic integration; the problems; SCO; immigration; cross-border rivers; the customs union.